2014
DOI: 10.2217/pgs.14.107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Platinating Agent and Taxane Pathway Genes as Predictors of Outcome and Toxicity in Advanced Non-Small-Cell Lung Cancer

Abstract: Aim Lung carcinoma is the most common malignancy and the leading cause of cancer deaths worldwide. Although clinical factors including age, performance status and stage influence the likelihood of benefit from and tolerability of chemotherapy, the genetic profile of individual patients may be an independent predictor of response and toxicity. The present study aimed to identify pharmacogenetic markers associated with clinical response and toxicity in patients with advanced non-small cell lung cancer (NSCLC) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 30 publications
2
59
1
Order By: Relevance
“…Recent ABCB1 SNPs are associated with platinum or gefitinib-induced ADR ABCB1 SNP rs1128503, in patients treated either with carboplatin plus adjuvant or cisplatin plus adjuvant, was associated with increased PFS irrespective of patient ethnicity [28]. This study, by Lamba et al, also showed an association between the ABCB1 SNP rs2235015 and platinum-induced thrombocytopenia (p = 0.04) [28].…”
Section: Abcb1 Abcb1 Publication Characteristicssupporting
confidence: 50%
See 2 more Smart Citations
“…Recent ABCB1 SNPs are associated with platinum or gefitinib-induced ADR ABCB1 SNP rs1128503, in patients treated either with carboplatin plus adjuvant or cisplatin plus adjuvant, was associated with increased PFS irrespective of patient ethnicity [28]. This study, by Lamba et al, also showed an association between the ABCB1 SNP rs2235015 and platinum-induced thrombocytopenia (p = 0.04) [28].…”
Section: Abcb1 Abcb1 Publication Characteristicssupporting
confidence: 50%
“…Meta-analysis is described for efflux transporter genes ABCB1 [19][20][21][22][23][24], ABCC1 [25][26][27][28][29], ABCC2 [20,28,[30][31][32], ABCG2 [19][20][21][22]24,25,[33][34][35][36]. A systematic review is given for efflux transporter genes ABCA1 [37,38], ABCC4 [39], ABCC5 [25], ABCC11 [40] and ABCC12 [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(22,23) Some studies in NSCLC have demonstrated that polymorphisms in drug-transporter genes (ABCB1 and ABCG2), DNA-repair pathway genes (ERCC4 and XCC), and apoptosis pathway genes (CASP 8 and CASP10) are associated with thrombocytopenia, neutropenia, and severe hematologic toxicity, respectively, due to paclitaxel-carboplatin effects. (24)(25)(26) One limitation of this study is the small sample size which was not appropriate to the estimated sample size due to incomplete data. Another limitation is inadequate hematologic data in each of the chemotherapy cycles, which limits statistical analysis; however, the decreasing trend in the hematologic data might be used to generalize the findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, polymorphism C37A (rs 12806698) in RRM1 gene was associated with higher incidence of vomiting and D1104H (rs17655) in ERCC5 gene-with susceptibility to infections. Lambet al [23] showed that SNPs in ERCC4 and XPC genes were significantly related to risk of neutropenia in 90 Caucasian male patients treated with the combination of carboplatin and paclitaxel. Wu et al [11] noted that the incidence of severe haematologic toxicity (especially leucopoenia) was significantly higher in the AA genotype carriers (396A [ C, rs238406) of XPD gene in 209 Asian NSCLC patients received chemotherapy based on platinum compounds.…”
Section: Discussionmentioning
confidence: 99%